2010
DOI: 10.1002/jso.21439
|View full text |Cite
|
Sign up to set email alerts
|

SPECT/CT for preoperative sentinel node localization

Abstract: The value of SPECT/CT for detection and localization of sentinel nodes is reviewed. SPECT/CT depicts extra sentinel nodes and identifies nonnodal tracer accumulation. SPECT/CT is indicated in patients with complex lymphatic drainage as often present in patients with head, neck and scapular melanoma, breast cancer patients with extra-axillary sentinel nodes and patients with tumors draining to pelvic nodes. SPECT/CT also clarifies the drainage pattern of inconclusive conventional images (non-visualization or un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(69 citation statements)
references
References 41 publications
2
65
0
2
Order By: Relevance
“…25) They found that SPECT/CT for SN mapping brought precise localization with three-dimensional imaging. Application of SPECT/CT to SN mapping might improve detection and localization even in esophageal cancer.…”
Section: Results Of Sentinel Node Biopsy For Esophageal Cancermentioning
confidence: 99%
“…25) They found that SPECT/CT for SN mapping brought precise localization with three-dimensional imaging. Application of SPECT/CT to SN mapping might improve detection and localization even in esophageal cancer.…”
Section: Results Of Sentinel Node Biopsy For Esophageal Cancermentioning
confidence: 99%
“…In this region, there are more complex lymphatic drainage patterns involving multiple lymph node basins, and the success of identifying SLNs may be lower than in other regions, particularly when the surgeon has less experience with head and neck SLNB. It has been proposed that the higher-resolution, three-dimensional images achieved with SPECT/CT imaging may enhance detection of SLNs and decrease risks by limiting the dissection necessary for SLNB [Even-Sapir et al, 2003;Roarke et al, 2007;Vermeeren et al, 2010], but this remains to be determined. Patients should be informed that an attempted SLNB may be unsuccessful, in which case the risks, cost, and discomfort associated with the procedure are incurred without added benefit to wide excision alone.…”
Section: Slnb For Head and Neck Melanomasmentioning
confidence: 99%
“…However, depending on the circumstances, a second injection may pose significant logistical problems for the patient, operating room, and surgeon. Alternatively, the procedure may be postponed in favor of repeating lymphoscintigraphy with SPECT/CT imaging, which provides a finer, threedimensional image of lymphatic drainage and may enhance the ability to detect SLNs in the setting of complex drainage patterns [van der Ploeg et al, 2009;Vermeeren et al, 2010]. This is more resource-intensive, however, and SPECT/CT imaging is not available at all institutions that offer lymphoscintigraphy.…”
Section: Complex Drainage Patters or Failure To Localize Sentinel Lymmentioning
confidence: 99%
“…[7] Since its introduction, hybrid SPECT/CT has been known as the most reliable imaging technique for showing the exact locations of SNs. [8] However, this new technology is only available at a few hospitals because of the high cost of the instrumentation. Thus, software-based coregistration of SPECT and CT images is still considered to be useful and more cost effective.…”
Section: Introductionmentioning
confidence: 99%